Analisis Gambaran Histopatologis pada Jaringan Kulit Rattus norvegicus yang Mengalami Kekerasan Tumpul Tanpa Jejas - Indrayana, Mohammad Tegar; Susanti, Rika; Syahputra, Roni Eka; Hillbertina, Noza; Afandi, Dedi; Yanwirasti, Yanwirasti; Irawati, Nuzulia; Amir, Arni (Fakultas Kedokteran Universitas Riau, 2024)
Blunt trauma without visible skin damage is a common type of violence encountered in physical assault cases. Statistically, at RS Bhayangkara Pekanbaru, 341 cases of blunt trauma without skin damage were reported out of a total of 6,255 assault cases from 2015 to 2020. These cases present a challenge for doctors in finding physical evidence of trauma to document in medicolegal reports (Visum et Repertum). This study aims to analyze the histopathological differences, including erythrocyte extravasation, neutrophil and monocyte cell infiltration, and tissue edema, between groups subjected to blunt trauma without skin damage and a control group. Using a post-test-only group design, this study involved 30 Rattus norvegicus samples divided into three groups: control, intervention group 1, and intervention group 2. The intervention involved a 324-gram load dropped from a height of 45 cm onto the surface of the rats' skin. Histopathological examination revealed no significant differences in erythrocyte extravasation, neutrophil infiltration, or monocyte infiltration, while a significant difference was observed in tissue edema levels.